Optimization of liquid state bioconversion process for microbial treatment of domestic wastewater sludge - Alam, Md. Zahangir; Fakhru’l-Razi, Ahmadun; Molla , Abul Hossain (NRC Research, 2003)
The evaluation of cheap carbon sources (co-substrate) and process conditions for microbial treatment of domestic wastewater sludge (DWS) was investigated using a liquid state bioconversion (LSB) laboratory scale process. Six cheap carbon sources were used: wheat flour (WF), rice flour (RF), corn flour (CF), sago starch (SS), cassava starch (CS), and commercial sugar (S). Process conditions such as co-substrate(s) concentration, temperature, initial pH, and inoculum size were optimized in terms of dry filter cake (DFC) production, removal of total suspended solids (TSS),turbidity (optical density against distilled water, 660 nm), and chemical oxygen demand (COD) in supernatant. The results obtained indicated that sludge containing wheat flour as a carbon source was a better co-substrate for microbial growth,with significant utilization for minimizing the dissolved and suspended materials in sludge. The optimized parameters for fungal treatment of DWS obtained were 1.5–2% (w/w) of WF concentration, temperature of 33–35◦C, initial pH of 4.5–5.5, and inoculum size of 2–3% v/w. Effective results for optimum values were recoded at 4 d of microbial treatment.